Tumor of the sternal region - Martínez, José Luis; Croci, Fabio; Belloso, Rogelio (Cirugía del Uruguay, 1982)
The authors present a rare histological variety of malignant skin tumor originated in sweat g!ands that showed a definite tendency towards local recidivation. The last recidivation affected the sternum that had to undergo partial resection. The tecnique used to reconstruct the sternal defect is presented.